Penerapan Model Pembelajaran Kooperatif Tipe Course Review Horay (CRH) untuk Meningkatkan Minat Belajar Ilmu Pengetahuan Alam dan Sosial - Eri Nuraeni (Universitas Palan, 2025)
This research is based on students' low interest in learning in Natural and Social Sciences (IPAS) subjects, which can be seen from the large number of students who obtain scores below the Learning Goal Achievement Criteria (KKTP). The focus of this research is to increase students' interest in learning through the application of the Course Review Horay (CRH) learning model in the material